Compliance with the EAT-Lancet diet and risk of colorectal cancer: a prospective cohort study in 98,415 American adults - Ren, Xiaorui; Yu, Chuanchuan; Peng, Linglong; Gu, Haitao; Xiao, Yi; Tang, Yunhao; He, Hongmei; Xiang, Ling; Wang, Yaxu; Jiang, Yahui (Frontiers in Nutrition, 2023)
Background: The EAT-Lancet diet (ELD) is a recommended dietary pattern for achieving simultaneous improvements in both individual health and environmental sustainability. While research on the association between ELD and colorectal cancer (CRC) remains scarce, the potential impact of nutrition on CRC prevention and progression is a topic of growing interest. This study aims to investigate the relationship between adherence to the ELD and the risk of CRC, shedding light on the role of nutrition in CRC prevention. Methods: Among 98415 included participants, Diet History Questionnaire (DHQ) was used to collect dietary information, ELD score was used to assess the adherence to ELD, higher scores indicated greater adherence. Cox hazards regression analyses were conducted to examine whether there were associations between ELD score and CRC risk. Restricted cubic spline (RCS) model was used to further explore the dose-response association between ELD score and CRC incidence. Subgroup analyses were conducted to identify potential modifiers interacted with ELD on CRC incidence, and sensitivity analyses were performed to evaluate the robustness of the established association. Results: During a mean follow-up of 8.82 years, a total of 1054 CRC cases were documented. We found statistically significant correlation between ELD score and CRC risk (Q4 vs Q1: HR 0.81, 95% CI 0.67-0.98; P for trend = 0.034) after adjusting for potential confounders. No statistically significant associations were discovered between ELD adherence and CRC by anatomical site. Subgroup analyses found no interactional factor, sensitivity analyses and RCS model showed a robustness and linearity association (P-linearity >0.05). Conclusion: We concluded that adherence to ELD contributes to the prevention of CRC.